Technology use and preferences for mental health self‐management interventions among older veterans. (29th December 2019) - Gould, Christine E.; Loup, Julia; Kuhn, Eric; Beaudreau, Sherry A.; Ma, Flora; Goldstein, Mary K.; Wetherell, Julie Loebach; Zapata, Aimee Marie L.; Choe, Philip; O'Hara, Ruth
Abstract : Objectives: The United States Department of Veterans Affairs offers numerous technology‐delivered interventions to self‐manage mental health problems. It is unknown, however, what barriers older military veterans face to using these technologies and how willing they would be to use technologies for mental health concerns. Methods: Seventy‐seven veterans (Mage = 69.16 years; SD = 7.10) completed interviews in a concurrent mixed methods study. Interviewers asked about technology ownership and described four modalities of delivering self‐management interventions: printed materials, DVDs, Internet, and mobile apps. Interviewers obtained feedback about each modality's benefits, barriers, and facilitators. Participants ranked their self‐management modalities preferences alone and compared with counseling. Multivariable adjusted logistic regression and qualitative analyses were conducted to investigate the reasons contributing to preferences. Results: Most reported owning a computer (84.4%), having home Internet (80.5%), and a smartphone (70.1%). Participants preferred printed materials (35.1%) over mobile apps (28.6%), Internet (24.7%), and DVDs (13.0%). Lower computer proficiency was associated with preferring DVDs; higher proficiency was associated with Internet and mobile interventions. Residing in an urban area was associated with mobile apps. When counseling was an option, 66% identified this as their first preference. Qualitative findings showed veterans' desire for information, training, and provider support with technology. Conclusions: Older veterans reported high technology ownership rates but varied preferences for self‐management interventions. Notably, two‐thirds preferred some form of technology, which points to the importance of ensuring that providers offer existing technology‐delivered interventions to older veterans. Veterans' strong preference for counseling emphasizes the need for human support alongside self‐management.